Iron deficiency and anemia are associated with low retinol levels in children aged 1 to 5 years - Bárbara C.A. Saraiva; Michele C.C. Soares; Luana C.dos Santos; Simone C.L. Pereira; Paula M. Horta (Elsevier, 2014)
Objective: To analyze the occurrence of anemia and iron deficiency in children aged 1 to 5 years and the association of these events and retinol deficiency. Methods: This was an observational analytic cross-sectional study conducted in Vitoria, ES, Brazil, between April and August of 2008, with healthy children aged 1 to 5 years (n = 692) that lived in areas covered by primary healthcare services. Sociodemographic and economic conditions, dietary intake (energy, protein, iron, and vitamin A ingestion), anthropometric data (body mass index-for-age and height-for-age), and biochemical parameters (ferritin, hemoglobin, and retinol serum) were collected. Results: The prevalence of anemia, iron deficiency, and retinol deficiency was 15.7%, 28.1%, and 24.7%, respectively. Univariate analysis showed a higher prevalence of anemia (PR: 4.62, 95% CI: 3.36, 6.34, p < 0.001) and iron deficiency (PR: 4.51, 95% CI: 3.30, 6.17, p < 0.001) among children with retinol deficiency. The same results were obtained after adjusting for socioeconomic and demographic conditions, dietary intake, and anthropometric variables. There was a positive association between ferritin vs. retinol serum (r = 0.597; p < 0.001) and hemoglobin vs. retinol serum (r = 0.770; p < 0.001). Conclusions: Anemia and iron deficiency were associated with low levels of serum retinol in children aged 1 to 5 years, and a positive correlation was verified between serum retinol and serum ferritin and hemoglobin levels. These results indicate the importance of initiatives encouraging the development of new treatments and further research regarding retinol deficiency. Resumo: Objetivo: Analisar a ocorrência de anemia e de deficiência de ferro em crianças de 1 a 5 anos e a associação destes desfechos com a deficiência de retinol. Métodos: Trata-se de um estudo observacional analítico do tipo transversal, realizado no município de Vitória - ES, entre abril e agosto de 2008, com crianças (n = 692) saudáveis de 1 a 5 anos, residentes em áreas de abrangência de Unidades Básicas de Saúde. Foram avaliados dados sociodemográficos, econômicos, dietéticos (ingestão de energia, proteína, ferro e vitamina A), antropométricos (índice de massa corporal-por-idade e estatura-por-idade) e bioquímicos (níveis séricos de ferritina, hemoglobina e retinol). Resultados: Detectou-se anemia, deficiência de ferro e deficiência de retinol em 15,7%, 28,1% e 24,7% das crianças, respectivamente. A análise univariada evidenciou maior ocorrência de anemia (RP: 4,62; IC 95%: 3,36; 6,34, p < 0.001) e de deficiência de ferro (RP: 4,51; IC 95%: 3,30; 6,17, p < 0.001) entre crianças que apresentavam deficiência de retinol. As mesmas relações se mantiveram após o ajuste pelas variáveis socioeconômicas, demográficas, dietéticas e antropométricas. Houve relação positiva entre os valores de ferritina sérica vs. retinol (r = 0,597; p < 0,001) e hemoglobina vs. retinol (r = 0,770; p < 0,001). Conclusões: A anemia e a deficiência de ferro mostraram-se associadas com baixos níveis de retinol em crianças de 1 a 5 anos, e houve correlação positiva dos níveis de retinol com os de ferritina sérica e hemoglobina. Isto torna importante iniciativas que estimulem o desenvolvimento de novos tratamentos e a ampliação de pesquisas em relação à deficiência de retinol. Keywords: Children, Iron deficiency anemia, Iron deficiency, Vitamin A, Palavras-chave: Crianças, Anemia ferropriva, Deficiência de ferro, Vitamina A